Patient‐led innovation and global health justice: Open‐source digital health technology for type 1 diabetes care. - Jansky, Bianca; Hendl, Tereza; Nocanda, Azakhiwe Z. (Bioethics, 2024)
Health innovation is mainly envisioned in direct connection to medical research institutions or pharmaceutical and technology companies. Yet, these types of innovation often do not meet the needs and expectations of individuals affected by health conditions. With the emergence of digital health technologies and social media, we can observe a shift, which involves people living with illness modifying and improving medical and health devices outside of the formal research and development sector, figuring both as users and innovators. This patient‐led innovation has been celebrated in innovation studies and economics as a "bottom‐up" type of innovation. In this article, we take a closer look at open‐source patient‐led innovation in the context of type 1 diabetes care. In our inquiry, we pay particular attention to the social and ethical dimensions of this innovation, building on empirical material. Upon exploring the notion of patient‐led innovation and its socio‐political context through the lens of intersectional and global health justice, we argue that a proactive strategy is needed to ensure that open‐source patient‐led innovation will be more globally accessible, center the health needs of the most underserved populations, as well as facilitate equitable and just health benefits. To support this aim, we provide a range of examples of different initiatives addressing the persistent inequalities that have so far inhibited patient‐led innovation from more fully materializing its innovative potential.